Promoting English Language Teaching through intercultural communication: A Case of Far Western University - Negi, Arjun Singh (Journal of Research in Education, 2025)
Language and culture are deeply interconnected. Culture finds its expression in language; so, learning a new language without familiarity with its culture remains incomplete. English speakers at present have dual challenges: one to be able to adopt in world cultures and to promote their local culture in comparison to other cultures. So the goal of English language teaching has undergone changes from imitating ’’native speakers’’ to becoming an intercultural communicator though pedagogical implementations have not been fully realized in classrooms, especially the ones that enable students to communicate globally while at the same time help them maintaining their native / traditional languages and cultures. The main purpose of this study is to explore lived experiences of Campus Level English teachers regarding the use of intercultural communication in ELT classes. To explore the issue the researcher has used Sociocultural theory (1962,1981) and Intercultural Competence model(1997b) for the observation of intercultural communication in ELT classes. The researcher has adapted an interpretive paradigm as the research design to guide the study and employed phenomenology as the research method. Five English language teachers of Central Campus of Far Western University are the participants for the study. As the data collection tools, in depth interview and personal narratives have been used. The participants are found positive in the use of intercultural communication for promoting English language teaching as well as in promoting their local cultures. The study will be useful for teachers, students, curriculum designers, as well as researchers. The research will be beneficial for teachers as they will learn some techniques to teach English and promote intercultural communication in the classrooms. Learners will develop knowledge of various cultures and be able to communicate successfully with the people of various linguistic and cultural backgrounds. Similarly curriculum designers will adopt various strategies to promote various cultures in syllabus designing.